Transformation of Mg-bearing minerals and its effect on slagging during the high-alkali coal combustion - Bowen Chen; Zhuo Xiong; Yongchun Zhao; Junying Zhang (Fuel Processing Technology)
To better understand the mineralogical, release-transformation patterns and ash deposition of Mg-bearing minerals, Wucaiwan Coal (WCW), Meihuajing Coal (MHJ), and slag of water wall from a power plant were collected and high-temperature ash transformation experiments were conducted. X-ray fluorescence (XRF), X-ray diffractometer (XRD), scanning electron microscope coupled with energy dispersive spectrometer (SEM-EDS), and simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC) were used to analyze the mineralogy, chemical composition, and characteristics. The results show that the Mg-bearing minerals in high-alkali coal and ash include dolomite, chlorite, forsterite, melilite, akermanite, diopside, bredigite, pyroxene, periclase, spinel, and magnesioferrite. During combustion, the release of Mg is affected by its mode of occurrence. Mg-bearing minerals gradually transform into thermally stable minerals, including spinel, periclase, and pyroxene, with the transformation pathway being dolomite → Mg-bearing silicate (diopside, akermanite, bredigite) → pyroxene/spinel/periclase. Moreover, Ca has a competitive and synergistic effect on the transformation of Mg-bearing minerals, which depends on the relative content of Si and Al in ash. Spinel is the primary Mg-bearing mineral in high-temperature ash, and Fe may substitute for both Mg and Al. In coal combustion, the formation of Mg-Al-Fe and Mg-Al-Fe-Si-Ca eutectic systems from Mg-bearing minerals causes slagging on the water wall and worsens water wall corrosion.